1999
DOI: 10.1093/sleep/22.4.475
|View full text |Cite
|
Sign up to set email alerts
|

Long Distance Driving and Self–Induced Sleep Deprivation among Automobile Drivers

Abstract: The results of the study highlight variables (long-distance driving, youth, sleep restriction) that are frequently associated with sleep-related accidents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 11 publications
1
52
0
Order By: Relevance
“…Working under sleep deprivation increases fatigue and risk of driver behavioral errors and violation [6-10, 25, 26]. RTCs from work to home is one of the major causes of injury and deaths among drivers [3][4][5][6][7]13] because of these conflicts between physiological needs and social or professional activities [27], understanding the human limits of fatigue and sleep deprivation are becoming key issues in accident prevention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Working under sleep deprivation increases fatigue and risk of driver behavioral errors and violation [6-10, 25, 26]. RTCs from work to home is one of the major causes of injury and deaths among drivers [3][4][5][6][7]13] because of these conflicts between physiological needs and social or professional activities [27], understanding the human limits of fatigue and sleep deprivation are becoming key issues in accident prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Studies largely conducted in high-income and middle income countries suggest driver sleepiness is a significant contributor to the burden of RTI (road traffic injuries) [1][2][3][4][5][6], with a three to six-fold increased risk of road crashes [2,3,13,14], and population attributable estimates as high as 22% [5,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We questioned, apart from organic sleep disorders, if modifications of the sleep-wake schedules could be responsible for sleepiness at the wheel. Studying large populations of drivers 6,7) , we demonstrated that long-distance driving was very frequently associated with sleep curtailment. Our first study performed on a freeway rest stop area in 1993, showed that 50% of drivers (n = 567 drivers) reduced their sleep duration in the 24 h before departure for a longdistance journey 6) .…”
Section: Sleepiness and Behaviourmentioning
confidence: 97%